The wall of storms - Liu, Ken, 1976- (Book two of the dandelion dynasty, 2016)
"In the much-anticipated sequel to the "magnificent fantasy epic" (NPR) Grace of Kings, Emperor Kuni Garu is faced with the invasion of an invincible army in his kingdom and must quickly find a way to defeat the intruders. Kuni Garu, now known as Emperor Ragin, runs the archipelago kingdom of Dara, but struggles to maintain progress while serving the demands of the people and his vision. Then an unexpected invading force from the Lyucu empire in the far distant west comes to the shores of Dara--and chaos results. But Emperor Kuni cannot go and lead his kingdom against the threat himself with his recently healed empire fraying at the seams, so he sends the only people he trusts to be Dara's savvy and cunning hopes against the invincible invaders: his children, now grown and ready to make their mark on history"--